Safe asset shortage and collateral reuse - Stephan Jank; Emanuel Mönch; Michael Schneider (Leibniz Institute for Financial Research SAFE, 2022)
The reuse of collateral can support the efficient allocation of safe assets in the financial system. Exploiting a novel dataset, we show that banks substantially increase their reuse of sovereign bonds in response to scarcity induced by Eurosystem asset purchases. While repo rates react little to purchase-induced scarcity when reuse is low, they become increasingly sensitive at high levels of reuse. An elevated reuse rate is also associated with more failures to deliver and a higher volatility of repo rates in the cross-section of bonds. Our results highlight the trade-off between shock absorption and shock amplification effects of collateral reuse.
Keywords: E4; E5; G1; G2; 330; safe assets; government bonds; collateral reuse; rehypothecation; repo market; securities lending